Influence of cellulose ethers on the kinetics of early Portland cement hydration - Müller, Ingo (Karlsruher mineralogische und geochemische Hefte, 2006)
The phase-specific influence of cellulose ether (CEs) on Portland cement hydration was investigated in-situ, using synchrotron X-ray diffractometry. CE-caused retardation can be traced to the polymers adsorption behaviour. The adsorption decreases in following order: silicates and their hydrates (high), sulfates (low), ettringite (zero). The retarding effect is strong on silicates, moderate on sulfates and unspecific on alluminates.